Policy Making for Global Transportation Planning using the Delphi-Scenario Writing with a New Concept of 'Future Vision' - Kawano Masaya; Koyanagi Kenta (European Regional Science Association (ERSA), 2005)
The personal trip survey plays a vital role in global, multi-modal transportation planning. The four-step method for estimating travel demand based on data from the personal trip survey has been systematized during the course of long-term studies and practical applications. This method therefore has been widely used in various aspects of transportation planning. However, it is usually concerned with travel demand and very useful in periods of economic expansion. Now that emphasis is being placed on quality because the economy has taken a downturn, the conventional method should be reconsidered in terms of a qualitative, political approach. The present study deals with a new methodology for establishing a qualitative, long-term view of regional requirements. In other words, the purpose of this study is to create a socio-economic vision of the future for proper transportation planning for a target region. This study calls it 'future vision', which consists of several future images when considering the changing characteristics of the region and relationship with surrounding areas. These future images can cover all transportation-related topics, from global problems to local issues. Each future image is composed of scenarios that reflect the future direction and role of transportation planning, which fully describes infrastructures as well as management. Transportation planning experts employed brainstorming to create an initial version of the future vision. The brainstorming brought many important keywords related to the future images. The planners assembled keywords and added sentences to set up scenarios. This version was revised by using the Delphi questionnaire method in order to eliminate obvious errors and improper perspectives, while incorporating missing information. The Delphi method was conducted on researchers, engineers, planners, and administrators that are well versed in transportation planning. A procedure was also developed to update almost automatically according to the results of the questionnaire. The revised version of the future vision was again checked and revised similarly by the Delphi method and the updating procedure. Actually, the future vision was refined twice, which led to the final version of the future vision having a high degree of accuracy and feasibility. The future vision is qualitative and policy-oriented, while the conventional four-step method is quantitative and demand-oriented. Two different approaches should work together for the comprehensive transportation planning. This study finally introduced a hybrid method between the two approaches by discussing a way of linking the future vision with the conventional personal trip survey system. The proposed linkage produced (1) hearing recommendations of various people in many positions, (2) enhancement of the transportation planning by sharing and solving anticipated problems, and (3) incorporation of more policy-oriented planning elements.
Keywords: 330